Evaluation of the conventional and rheological properties of SBS plus Sasobit modified binder - Kok, Baha Vural; Yilmaz, Mehmet; Akpolat, Mustafa (Elsevier Sci Ltd, 2014)
The effort of constructing durable roads with higher standards has required to research the usage of various additives in bituminous coating so far. Nowadays polymer modification is effectively applied, and additives, which can provide better compaction and less expense by improving workability features are considered. These additives contribute to performance as well as workability. In this study conventional and rheological properties of binders, which include styrene-butadiene-styrene (SBS) in various rates and an organic warm mixture additive (Sasobit (R)), are investigated. The effects of additives, which are used separately and together in the binder are examined. As a result, it was found out that warm-mix-additive modification has better performance than SBS modification in terms of temperature susceptibility and SBS modification has better than Sasobit modification in terms of rutting parameter especially in high temperatures. Also, Sasobit (R) modification significantly decreased the viscosity and increased the softening point compared to SBS modification. The results show that the properties of the bitumen modified with combined additives are significantly different from that of individually modified bitumen. If additives are used in the same mixture together, warm-mix-additive can be added in certain ratios into SBS modification in order to obtain same properties stated above. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: SOS; Sasobit; Temperature susceptibility; Rheological properties